Діагностика та лікування солітарних кістозних вузлів щитоподібної залози - Павловський, М. П.; Коломійцев, В. І.; Маріна, В. Н.; Костюк, О. В.; Довгань, Ю. П. (Clinical Endocrinology and Endocrine Surgery, 2009)
In our research work we analysed 336 cases of cysttrasformated goiter. Patients were treated in the department of faculty surgery of Lviv national medical university by Danylo Galytski during 2003-2007 years. Approach to the method of treatment ot cyst nodules was proposed according to its structure. We prooved efficiency of preoperative diagnostic and showed result of treatment.